Litter and plastic monitoring in the Indian marine environment: A review of current research, policies, waste management, and a roadmap for multidisciplinary action. (March 2022) - Sivadas, Sanitha K.; Mishra, Pravakar; Kaviarasan, T.; Sambandam, M.; Dhineka, K.; Murthy, M.V. Ramana; Nayak, Shailesh; Sivyer, David; Hoehn, Danja
Abstract: Environmental contamination due to plastic waste mismanagement is a growing global concern. Plastic problem is of particular concern to the Indian Ocean nations as Asia currently contributes to the highest share of mismanaged plastic waste. Consequently, there is a worldwide interest to understand the distribution and transboundary movement of plastic from this region, which is crucial for implementing management measures. This review article focuses on current knowledge of plastic research, policies, waste management, socio-economics, challenges, and research opportunities. To date, marine plastic studies have focused on a few locations, providing an analysis of distribution and plastic–organism interactions in the Indian marine system. Along with scientific investigation, enforcement, improvisation, and, if necessary, framing new policies, integrated technologies to manage plastic waste, and behavioural changes are essential to mitigate plastic pollution. Such measures will be effective through a combination of actions among national and international researchers, industries, environmental managers, and the public. Highlights: Limited studies exist on litter and plastic from the Indian marine system. Studies mostly focussed on litter and microplastics from beaches and coastal environment. Future studies need to focus on source-sink dynamics, spatio-temporal variability, toxicity on organisms, and human health. A network of scientists, policymakers, industries, and the general public is critical for marine litter management.